G-flux, supersymmetry and Spin(7) manifolds - Acharya, B; De la Ossa, X; Gukov, S (2002)
In this note we study warped compactifications of M-theory on manifolds of Spin(7) holonomy in the presence of background 4-form flux. The explicit expression for the superpotential can be given in terms of the self-dual Cayley calibration on the Spin(7) manifold, in agreement with the general formula proposed in hep-th/9911011. © SISSA/ISAS 2002.